Implementasi Reformasi Birokrasi Dalam Pengembangan Sumber Daya Manusia Aparatur Di Dinas Koperasi Usaha Kecil Menengah dan Perdagangan Kabupaten Dharmasraya - Widya Cahyani; Syamsir Syamsir (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research aims to find out how bureaucratic reform is implemented in developing human resources for the apparatus at the Dharmasraya Regency Small and Medium Enterprises Cooperatives and Trade Service. Researchers conducted qualitative research using descriptive methods. The research was conducted at the Dharmasraya Regency Small and Medium Enterprises Cooperatives and Trade Service. To select informants using purposive sampling. The data sources for this research are primary and secondary data, which were collected through interviews and documentation. However, triangulation of methods and sources is used to test the validity of the data. Data analysis consists of four stages: data collection, data reduction, data delivery and conclusions. The research results show that the implementation of bureaucratic reform in the development of human resources for the apparatus has gone well, although not optimally. employee skills are still lacking, thus explaining the importance of providing training to State Civil Servants who need it. The Dharmasraya Regency Small and Medium Enterprises Cooperatives and Trade Service has implemented bureaucratic reform in the aspect of human resource development. There are three indicators in human resource development according to Lijan Poltak Sinambela (2016), namely (1) Training and development of human resources such as training for civil servants (Laksa), career advancement training, (2) Compensation (3) Career development. Meanwhile, in the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 18 of 2021 concerning the Road Map for Bureaucratic Reform of the Ministry of State Apparatus Empowerment and Bureaucratic Reform for 2020-2024, there are seven indicators of success in developing human resources, namely (1) Planning employee needs (2 ) Employee recruitment (3) Employee development (4) Promotion, transfer and rotation of employees (5) Implementation of employee performance assessments (6) Enforcement of employee code of ethics (7) Developing a personnel information system. However, in implementing bureaucratic reform, the Dharmasraya Regency Cooperatives, Small and Medium Enterprises and Trade Service experienced obstacles, such as a lack of infrastructure, a lack of budget, and a lack of training provision for ASN. Efforts made by the Dharmasraya Regency Small and Medium Enterprises Cooperatives and Trade Service are (1) Development through Training (2) Increasing human resource capacity in the region (3) Human resource training system